X‐ray nanodiffraction analysis of stress oscillations in a W thin film on through‐silicon via. (21st January 2016) - Todt, J.; Hammer, H.; Sartory, B.; Burghammer, M.; Kraft, J.; Daniel, R.; Keckes, J.; Defregger, S.
Abstract : X‐ray nanodiffraction is used to evaluate axial and tangential residual stress distributions in a W thin film deposited on the scalloped inner wall of a through‐silicon via. The results reveal oscillatory stress distributions which correlate well with the scallop wavelength and morphology. Abstract : Synchrotron X‐ray nanodiffraction is used to analyse residual stress distributions in a 200 nm‐thick W film deposited on the scalloped inner wall of a through‐silicon via. The diffraction data are evaluated using a novel dedicated methodology which allows the quantification of axial and tangential stress components under the condition that radial stresses are negligible. The results reveal oscillatory axial stresses in the range of ∼445–885 MPa, with a distribution that correlates well with the scallop wavelength and morphology, as well as nearly constant tangential stresses of ∼800 MPa. The discrepancy with larger stress values obtained from a finite‐element model, as well as from a blanket W film, is attributed to the morphology and microstructural nature of the W film in the via.